HYDROGEOLOGICAL CHARACTERISTICS OF THE CENOMANIAN-ALBIAN AQUIFER IN THE INTERFLUVE OF THE RIVERS PAZHA AND TORGOSHA (SERGIEV POSAD DISTRICT OF THE MOSCOW REGION) - N. V. Fisun (Известия высших учебных заведений: Геология и разведка, 2018)
Currently, an interest in the underground waters of the Cenomanian-Albian horizon has increased significantly. And this is mainly due to the fact that numerous centers of discharge of the groundwater are the object of recreation, places of worship and are actively used by the population for drinking purposes. The geological and hydrogeological features of the studied horizon in the area between the rivers of the Pazha and Torgosha has been reviewed, still poorly understood. We have investigated the formation of the groundwater resources of the Cenomanian-Albian horizon and hydraulically related waters of Quaternary deposits that are the between the rivers of the Pazha and Torgosha. For the first time, based on the actual material, a map of hydroisohypses of the groundwater have been made, the parameters of filtration and capacitive properties of the Cenomanian-Albian horizon have been pointed out, an actual data on the quality and salt composition of the groundwater has been presented. The lack of study of this issue, the importance of further research in this direction, the need of monitoring the quality of groundwater and regulating the attendance of sources by tourists and local people to create safe conditions for their use have been notified.